Singular Value Decomposition-Based Method for Sliding Mode Control and Optimization of Nonlinear Neutral Systems - Heli Hu; Dan Zhao; Qingling Zhang (Journal of Applied Mathematics)
The sliding mode control and optimization are investigated for a class of nonlinear neutral systems with the unmatched nonlinear term. In the framework of Lyapunov stability theory, the existence conditions for the designed sliding surface and the stability bound α∗ are derived via twice transformations. The further results are to develop an efficient sliding mode control law with tuned parameters to attract the state trajectories onto the sliding surface in finite time and remain there for all the subsequent time. Finally, some comparisons are made to show the advantages of our proposed method.